(untitled) (Fiep Bulletin - online, 2014)
The theme of this text tries to reach a discussion process about how takes place the corporal significance in the classroom among each one of its social actors and also how is processed the respect one another while a being that is body. The development or self-consciousness of their own corporeity suggests that the process occurs in that group as a social product flowered from the personal interrelations and that they constitute fundamental and indissociated in identity formation of students and teachers involved in that process.